Synthesis And Characterization Of Zno Nanostructures Using Physical Vapor Deposition And Electrochemical Deposition For Optoelectronic Applications - Hassan, Nadim Khalid (2013)
ZnO nanostructures were grown by simple techniques to develop ZnO-based semiconductor photodetectors (PDs) for UV detection. This work employed two techniques, first, physical vapor deposition (PVD) and second, electrochemical deposition (ECD) techniques. In the PVD process, condensed Zn vapor is reacted with oxygen via vapor solid mechanism in three-zone tube furnace. The source material for PVD was pure Zn powder evaporated under different reaction conditions. Variations in the reaction time, substrates, and temperature in the furnace were found to control the growth mechanism and morphology of the ZnO nanostructures. For instance, high quality 1D ZnO nanostructures (Rods) were achieved on SiO2 using ZnO thin film as a buffer layer. Also, it was possible to grow tetrapods-like ZnO (TPs) and nanowires with different diameters and lengths as confirmed via SEM imaging. Photoluminescence (PL) measurements at room temperature showed a dominant peak related to a near-band-edge emission at approximately 376 nm with an additional peak related to green-band emission at approximately 520 nm.The highest near-band emission to green band emission ratio of 1D ZnO nanostructures grown on Si(111) could result from the high crystallinity of the fabricated nanostructure. Raman spectra measurements show four peaks, of which E2 high was the dominant peak. The shift in this dominant peak from 437 cm-1 provided accurate information of the stress in the ZnO film lattice.